(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Relevance of the topic: The prenatal period represents a critical stage of central nervous system development, during which the fetal brain demonstrates high sensitivity to adverse environmental influences. Chronic stress during pregnancy is considered one of the significant risk factors capable of disrupting neurodevelopment through neuroendocrine, metabolic, and inflammatory mechanisms. Elevated maternal stress hormones may interfere with normal brain maturation, leading to persistent structural and functional abnormalities. Among various brain regions, the cerebellum plays an essential role not only in motor coordination but also in cognitive and emotional regulation, making it particularly vulnerable to prenatal stress exposure. However, the structural consequences of chronic prenatal stress on cerebellar development remain insufficiently investigated.